Review on Airborne Nodes for Unmanned Aerial Vehicles (UAV) - Babikir, Edriss Eisa (IRO Journal on Sustainable Wireless Systems, 2024)
Airborne nodes are devices positioned in the air, most often on unmanned aerial vehicles (UAVs) or drones. Each of these nodes have been fitted with numerous sensors, communication devices, and computing capability to carry out specific activities or operations. Airborne node deployment involves several obstacles, including managing power, ensuring communication reliability, maintaining autonomy, and complying with legal regulations. However, technological breakthroughs are continually enhancing their capabilities and expanding their potential uses. The study presents an overview of airborne nodes by reviewing existing works, specifically focusing on Unmanned Aerial Vehicles (UAVs).